Association of Exclusive Breastfeeding to the Prevention of Precocious Puberty - Tjahyanto, Teddy; Angellina Mulyadi, Eunike; Angelica Novian, Gabriel; Rianto, Louis (Jurnal KESANS : Kesehatan dan Sains, 2023)
Introduction: Exclusive breastfeeding is breast milk given without other foods to children up to 6 months of age. Breast milk has many uses, including helping children's growth and development, preventing infections, reducing the risk of obesity, and helping children's mental and psychomotor development. Exclusive breastfeeding was found to have a protective effect against the incidence of precocious puberty. Precocious puberty is defined as the onset of puberty that occurs before age 8 in girls and age 9 in boys.  Objective: Based on these findings, the authors want to make a study to compile the latest research results on the association of exclusive breastfeeding as one of the prevention of precocious puberty.  Method: The author searches, selects, and selects journals related to exclusive breastfeeding with the prevention of precocious puberty through several research databases including ScienceDirect, Google Scholar, PubMed, and Wiley. The keywords used are "exclusive breastfeeding", "precocious puberty", and "prevention".  Results and discussion: Various studies have shown that exclusive breastfeeding has a protective effect against the incidence of precocious puberty. Exclusive breastfeeding alone can reduce the risk of obesity in children. Obesity in this child, based on several studies, is a risk factor for precocious puberty. Conclusion: Exclusive breastfeeding of children can prevent the incidence of precocious puberty.